Thrombotic Microangiopathy, an Unusual Form of Monoclonal Gammopathy of Renal Significance: Report of 3 Cases and Literature Review - Filippone, Edward J.; Newman, Eric D.; Li, Li; Gulati, Rakesh; Farber, John L. (Frontiers in Immunology, 2021)
Monoclonal gammopathies result from neoplastic clones of the B-cell lineage and may cause kidney disease by various mechanisms. When the underlying clone does not meet criteria for a malignancy requiring treatment, the paraprotein is called a monoclonal gammopathy of renal significance (MGRS). One rarely reported kidney lesion associated with benign paraproteins is thrombotic microangiopathy (TMA), provisionally considered as a combination signifying MGRS. Such cases may lack systemic features of TMA, such as a microangiopathic hemolytic anemia, and the disease may be kidney limited. There is no direct deposition of the paraprotein in the kidney, and the presumed mechanism is disordered complement regulation. We report three cases of kidney limited TMA associated with benign paraproteins that had no other detectable cause for the TMA, representing cases of MGRS. Two of the cases are receiving clone directed therapy, and none are receiving eculizumab. We discuss in detail the pathophysiological basis for this possible association. Our approach to therapy involves first ruling out other causes of TMA as well as an underlying B-cell malignancy that would necessitate direct treatment. Otherwise, clone directed therapy should be considered. If refractory to such therapy or the disease is severe and multisystemic, C5 inhibition (eculizumab or ravulizumab) may be indicated as well.